2021
DOI: 10.1002/brb3.2063
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis executive protein GSDMD as a biomarker for diagnosis and identification of Alzheimer’s disease

Abstract: Objective This study was mainly conducted to explore the expression changes of GSDMD and conventional markers (including T‐Tau, Tau181p, and Aβ1–42) in the cerebrospinal fluid among patients with Alzheimer's disease (AD) and vascular dementia (VD), followed by determination of role of GSDMD in diagnosing and identifying AD and VD. Methods In this study, 60 patients with VD, 60 patients with AD, and 50 healthy controls were enrolled. Lumbar puncture was performed to collect cerebrospinal fluid samples. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
(22 reference statements)
1
31
0
Order By: Relevance
“…While there is some indirect evidence implicating tau and activation of regulated forms of necrosis like pyroptosis [ 32 ], parthanatos [ 33 ] and ferroptosis [ 34 , 35 ], reviewed in [ 5 ], necroptosis has been more directly implicated in AD. Initial studies were based on the elevated expression of RIPK1 that correlated with Braak staging [ 36 ].…”
Section: Tau Aggregation or Pathology And Regulated Types Of Necrosis – Focus On Necroptosismentioning
confidence: 99%
“…While there is some indirect evidence implicating tau and activation of regulated forms of necrosis like pyroptosis [ 32 ], parthanatos [ 33 ] and ferroptosis [ 34 , 35 ], reviewed in [ 5 ], necroptosis has been more directly implicated in AD. Initial studies were based on the elevated expression of RIPK1 that correlated with Braak staging [ 36 ].…”
Section: Tau Aggregation or Pathology And Regulated Types Of Necrosis – Focus On Necroptosismentioning
confidence: 99%
“…Therefore, death neuronal is a root reason for AD and other neurodegenerative diseases (Hambright et al, 2017). Furthermore, emerging evidence indicates pyroptosis may serve as the predominant form of neuronal death in AD following apoptosis, autophagy, and necrosis (Fricker et al, 2018;Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, caspase activation has been defined as firstly recognizing the substrates’ tetrapeptide, XXXD (D is aspartic acid, X is other amino acid), and then cutting the specific peptide bond after D. The research of Feng Shao found that the recognition of GSDMD by caspase did not depend on the sequence characteristics of the tetrapeptide, but specifically directly recognized the C-terminal domain of GSDMD ( Wang K. et al, 2020 ). Studies have found that the expression level of GSDMD in the cerebrospinal fluid of AD patients was significantly higher than that of the general control group, and positively related to the release level of inflammatory factors, implying GSDMD could basically be applied as a diagnostic index of AD ( Shen et al, 2021 ). Other than GSDMD, recently, researches confirmed that GSDME also activated pyroptosis.…”
Section: Pyroptosismentioning
confidence: 99%